Halogen‐Bond Mediated 3D Confined Assembly of AB Diblock Copolymer and C Homopolymer Blends. Issue 18 (18th March 2021) - Zheng, Xihuang; Ren, Min; Wang, Huayang; Wang, Huiying; Geng, Zhen; Xu, Jiangping; Deng, Renhua; Chen, Senbin; Binder, Wolfgang H.; Zhu, Jintao
Abstract: Halogen‐bond driven assembly, a world parallel to hydrogen‐bond, has emerged as an attractive tool for constructing (macro)molecular arrangement. However, knowledge about halogen‐bond mediated confined‐assembly in emulsion droplets is limited so far. An I …. N bond mediated confined‐assembly pathway to enable order‐order phase transitions is reported here. Compared to hydrogen bonds, the distinct features of halogen bonds (e.g., higher directionality, hydrophobicity, favored in polar solvents), offers opportunities to achieve novel nanostructures and materials. Polystyrene‐ b ‐poly(4‐vinyl pyridine) (PS‐ b ‐P4VP) AB diblock copolymer is chosen as halogen acceptor, while an iodotetrafluorophenoxy substituted C‐type homopolymer, (poly(3‐(2, 3, 5, 6‐tetrafluoro‐4‐iodophenoxy)propyl acrylate), PTFIPA) is designed as halogen donor, synthesized via reversible addition‐fragmentation chain transfer (RAFT) polymerization. Formation of halogen bonding donor–acceptor pairs between the PTFIPA homopolymer and the P4VP segments presented in PS‐ b ‐P4VP, increase the volume of P4VP domains, in turn inducing an order‐to‐order morphology transition sequence: changing from spherical → cylindrical → lamellar → inverse cylindrical, by tuning the PTFIPA content and choice of surfactant. Subsequent selective swelling/deswelling of the P4VP domains give rise to further internal morphology transitions, creating tailored mesoporous microparticles, disassembled nanodiscs, and superaggregates. It is believed that these results will stimulate further examinations of halogen bonding interactions in emulsion droplets and many areas of application. Abstract : Halogen bonding interactions give rise to a profound picture of order‐to‐order morphology transition sequence under 3D confinement, changing from spherical → cylindrical → lamellar → inverse cylindrical, by tuning halogen donor content and the choice of surfactant. Subsequent selective swelling/deswelling of P4VP domains lead to further internal morphology transitions, creating tailored mesoporous microparticles, dis‐assembled nanodiscs, and superaggregates.